2016
DOI: 10.1038/cddis.2016.436
|View full text |Cite
|
Sign up to set email alerts
|

RanBP9/TSSC3 complex cooperates to suppress anoikis resistance and metastasis via inhibiting Src-mediated Akt signaling in osteosarcoma

Abstract: Suppression of anoikis is a prerequisite for tumor cell metastasis, which is correlated with chemoresistance and poor prognosis. We characterized a novel interaction between RanBP9 SPRY domain and TSSC3 PH domain by which RanBP9/TSSC3 complex exerts transcription and post-translation regulation in osteosarcoma. RanBP9/TSSC3 complex was inversely correlated with a highly anoikis-resistant phenotype in osteosarcoma cells and metastasis in human osteosarcoma. RanBP9 cooperated with TSSC3 to inhibit anchorage-inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 48 publications
3
35
0
4
Order By: Relevance
“…In particular, it may favor vesicle trafficking such as the gephyrin-mediated transport of GABA receptors to the surface membrane helped by dynactin, Kif5, and Hap1 23 , 24 and nucleocytoplasmic shuttling mediated by Ran-binding proteins (RANBP) 25 . PI3K activation may also promote the activation of Src-integrin complex which in turn confers anti-anoikis properties 26 , 27 . In particular, the Src-integrin complex together with ranbp9 may favour endocytosis, which is anti-amyloidogenic 28 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it may favor vesicle trafficking such as the gephyrin-mediated transport of GABA receptors to the surface membrane helped by dynactin, Kif5, and Hap1 23 , 24 and nucleocytoplasmic shuttling mediated by Ran-binding proteins (RANBP) 25 . PI3K activation may also promote the activation of Src-integrin complex which in turn confers anti-anoikis properties 26 , 27 . In particular, the Src-integrin complex together with ranbp9 may favour endocytosis, which is anti-amyloidogenic 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The proliferation of osteosarcoma cells was inhibited by TIMP3 overexpression, whereas TIMP3 knockdown had an antagonistic effect. Akt signaling has been reported to play essential roles in the progression of many tumors, including osteosarcoma ( Keremu et al, 2017 ; Liu et al, 2017 ; Ma et al, 2017 ), and the PI3K/Akt pathway participates in almost all malignant processes, including tumorigenesis, cancer cell proliferation, metastasis, angiogenesis, and chemoresistance ( Yuan and Cantley, 2008 ; Berlanga et al, 2016 ; Dai et al, 2016 ; Davaadelger et al, 2016 ). Our results showed that the p-Akt level correlated negatively with TIMP-3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Src was the first oncogene to be discovered with tyrosine kinase activity to activate the Akt pathway [ 45 ], and leads to anchorage-independent growth and anoikis resistance [ 46 ]. Studies from our lab indicate that TSSC3 binds to Src with Ranbp9 and prevents its phosphorylation, resulting in apoptosis [ 47 ], which prompted us to hypothesize that TSSC3 inhibition of Nanog expression was likely mediated by Src inactivation. We then demonstrated that overexpression of TSSC3 inactivates the Src/Akt pathway, and Src inactivation in OS cells inhibits Nanog expression.…”
Section: Discussionmentioning
confidence: 99%